THE ROLE OF HUMAN CAPITAL PERFORMANCE IN INDONESIA IN PRIVATE UNIVERSITIES FOR ADVANCING THE ASEAN 2045 VISION - Khaeruman Khaeruman; Irma Nurmala Dewi; Zainudin Hassan (Yayasan Education and Social Center, 2026)
This study aims to analyze the performance of human capital in private universities in Indonesia to advance the ASEAN Vision 2045. Human capital is a strategic asset that determines the competitiveness of higher education institutions by developing competencies, fostering innovation, enhancing academic productivity, and enabling adaptability to changes in the global environment. The research uses a qualitative, descriptive approach. Data collection was conducted through in-depth interviews, observations, and document analysis at several private universities in Indonesia. The research informants were university leaders, human resource managers, lecturers, education staff, and international cooperation managers, selected through purposive sampling. Data analysis was conducted using NVivo software across the stages of open coding, axial coding, and selective coding to identify the main themes of the study. The study's results show that human resource competence, digital transformation, knowledge management, and organizational innovation are the main factors affecting human capital performance. In addition, private universities are well positioned to support the ASEAN Vision 2045 through talent development, academic innovation, and digital transformation. However, there are still challenges in the form of low international collaboration, ASEAN academic mobility, and gaps in the quality of human resources between universities. Therefore, a sustainable human capital development strategy is needed to enhance Indonesia's higher education competitiveness in the ASEAN region.